REGULASI DAN PRAKTIK TRANSFER PRICING DI INDONESIA DAN NEGARA MAJU - SEPTARINI, NISA (Jurnal Akuntansi AKUNESA, 2012)
Transfer pricing is a price transaction happened between companies with special relationship. It could be conducted among others with taxes motivation, in which the main objective is to transfer the tax burden from the higher rated country to the lower rate jurisdiction. Provisions of the Act confirms KUP transfer pricing practice is a form of tax planning that does not violate the terms of taxation. Transfer pricing is categorized as a crime if it cost the state to avoid taxes. Then the formulation of the problem under study is how the transfer pricing regulations and practices in Indonesia and developed countries. The goal is to see the extent of his experience of transfer pricing practices. Conclusions can be drawn, namely Japan and the United States has implemented transfer pricing practices in accordance with the provisions and the OECD guidelines in optimizing Advance Pricing Arrangement (APA). Therefore, Indonesia should refer to the two countries in the practice of transfer pricing regulations, because until now has not made the rules of procedure.Keywords : transfer pricing, OECD guidelines, taxation.